Arthroscopic Bennett Lesion Resection: A Novel Technique - Samuel C. Hammonds MD; R. Alexander Creighton MD, CAQSM (SAGE Publishing, 2021)
Background: Bennett lesion is ossification of the posterior inferior glenohumeral ligament complex. Though often asymptomatic, these lesions can become painful and interfere with throwing ability. Indications: The Bennett lesion is relatively common among elite throwers, present in 22% to 25% of asymptomatic pitchers. Suggested causes of this lesion include traction on the posterior joint and posterior impingement in the late cocking phase. These lesions can become painful due to displacement and irritation of the joint capsule and axillary nerve. Therefore, efficient arthroscopic treatment of symptomatic lesions is essential. Technique Description: The patient is positioned in the lateral decubitus position, and the glenohumeral joint is accessed via posterior and anterior portals. Once the lesion is identified, it may be probed and debrided via the posterior portal. A posterior capsular release is performed, and 4.0 mm burr resection of the lesion is started, viewing from the anterior portal with a 70° arthroscope. Direct visualization through the posterior portal can be used to verify complete lesion resection. If there is a true tear of the posterior labrum, this can be repaired with a knotless suture anchor back to the glenoid, but usually there is delamination that can be left alone after addressing the Bennett lesion. Results: We have found good success treating Bennett lesions via the above technique. This is supported by previous literature as well, with return to preinjury levels ranging from 69% to 85% following arthroscopic resection. Discussion/Conclusion: Four diagnostic criteria have been described to ensure accurate diagnosis: detection of a bony spur at the posterior glenoid rim on plain x-ray films, best seen on Stryker notch and Bennett view; posterior shoulder pain while throwing; tenderness at the posteroinferior aspect of the glenohumeral joint; and improvement in pain following lidocaine injection. Magnetic resonance imaging is also an excellent diagnostic tool to detect early enthesopathic changes in the posterior glenoid or periosteum, as well as labral pathology. Following arthroscopic resection, 88% of patients were satisfied with their treatment when using these diagnostic criteria. Accurate diagnosis and efficient treatment of Bennett lesions are imperative in the throwing athlete, and when performed correctly, our technique provides significant and lasting improvement for patients.